Analisis Manajemen Risiko Terhadap Keberlangsungan Usaha UMKM Kos-kosan di Kota Bandung (Kosan OYE) - Marlina, Auriel Putri; Murdani, Yusuf; Ibrahim, Hammam Rizky (Universitas Serambi Mekkah, 2024)
Every business that is undertaken will irnevitably face competition in order to grow. Small and medium enterprises, commonly referred to as SMEs, are businesses that are relatively easy for anyone with the desire to start a business to run. Competition will always exist in every aspect of life, including SMEs. Every business faces competition and challenges that must be addressed. To deal with competition and challenges in the business world, every SME must conduct market research and develop human resources and technology. Every business also involves risk. Therefore, SMEs need to understand what risk management is. Risk management is necessary to anticipate or reduce the likelihood of risks occurring in a business. This paper aims to describe the risks faced by the SME boarding house